Application of Oli-Paradigm of German FDI Inflows in Turkey - Erkan Ilgün; Kasim Tatic (Economic Review: Journal of Economics and Business, 2012)
Foreign direct investment (FDI) plays a pivotal role in economic development. Most important advantages of this are new technology, management ability, marketing ability and modern know-how. However, the literature dealing specifically with the issue of German direct investments in Turkey is fairly sparse. Regarding this, the purpose of study is not only to explore the main determinants of German FDI inflows in Turkey, but also to increase our understanding of the relationship between FDI and its determinants. The conceptual framework used in this study was firstly designed by Dunning and became known as "The eclectic paradigm of international production". The results of a literature review about the German direct investments made in Turkey and the determinants of FDI related to the market entry are shown in the text. Portfolio investments as well as foreign debt are ignored. When considering market policy, there are numbers of investment motives that are critical for German companies, i.e. management potential and popularity. The entrepreneurs believe in "market potential, dynamics, growth", existing "High-and lows-killed" workers and "Political and economic stability" in Turkey. From the characterization of German direct investments, it is possible to conclude that the transfer of factors that influence competitiveness of German companies is major priority of companies positioned in Turkey. According to survey results, in majority of cases most advanced technology was transferred to Turkey.
Keywords: F16; F23; F53; 330; FDI; OLI-Paradigm; Turkey-Germany Relationship